Insecticide Activity Extract of Tinospra crispa Mixed With Cow Urine on Spodoptera litura in the Laboratory - Putri Mustika Sari; Henny Wahyunita; Adriansyah Yoesoep; Lisdayani; Fitra S. Harahap (Talenta Publisher, 2019)
Armyworms (Spodoptera litura) become important pests in Indoensia that eat leaves compared to other pests because they are polyfag. S. litura can reduce productivity even crop failure. Therefore, it is necessary to do research on how to control S. litura effectively and environmentally friendly. This study aims to determine the effectiveness of brotowali extract (Tinospra crispa) as a botanical insecticide and obtain the right concentration of fruit extract, young leaves, and old Brotowali leaves to control the armyworm (litura Spodopter). This study used a Non Factorial Completely Randomized Design (RAL) with 6 treatments of various doses of brotowali extract mixed with cow urine and 4 replications. The results of the study showed that the administration of Brotowali + Urine Cattle extract with high doses (30 ml / jar) was able to increase the speed of death of the armyworm.